Internship program: a bridge to close the gap between theory and practice / Marziah Mokhtar and Fauziana Fauzi @ Mat - Mokhtar, Marziah; Fauzi @ Mat, Fauziana (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2019)
Higher Learning Institutions today are increasingly required to produce highly mobile graduates able to respond to the ever changing needs of the contemporary workplace. Through industrial training, interns will be exposed to ethical values and good working practices as well as to help them understand the safety practices and regulations inside the industry and to instill the spirit of teamwork and good relationship between interns and employees. The motivation for the current research study is to examine the implementation of industrial training conducted by Faculty of Business and Management of Universiti Teknologi MARA and industrial perception on Business Students during their practical period. This research is also prompted by the concern in the increasing number of unemployed among fresh graduates. Feedback from industries would give a better picture of what is required of students since employers are increasingly looking beyond a graduate's academic knowledge. Results show that interns are flexible towards task assigned, committed and resourceful towards work. However, their level of problem solving and analytical skills were low and they also lacked communication skills. It is anticipated that this exploratory study will enable the academia to bridge the gap between theory and practice thus improving the curricula towards developing successful professional business graduates.